2013
DOI: 10.1371/journal.pone.0075303
|View full text |Cite|
|
Sign up to set email alerts
|

Non-Secreted Clusterin Isoforms Are Translated in Rare Amounts from Distinct Human mRNA Variants and Do Not Affect Bax-Mediated Apoptosis or the NF-κB Signaling Pathway

Abstract: Clusterin, also known as apolipoprotein J, is expressed from a variety of tissues and implicated in pathological disorders such as neurodegenerative diseases, ischemia and cancer. In contrast to secretory clusterin (sCLU), which acts as an extracellular chaperone, the synthesis, subcellular localization and function(s) of intracellular CLU isoforms is currently a matter of intense discussion. By investigating human CLU mRNAs we here unravel mechanisms leading to the synthesis of distinct CLU protein isoforms a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
74
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(77 citation statements)
references
References 70 publications
2
74
1
Order By: Relevance
“…Its strongest association was found for the common single nucleotide polymorphism (SNP) rs11136000 located in a non-coding, intronic CLU region [32]. CLU expression is highest in the brain and is markedly up regulated under situations of stress and inflammation .This gives rise to glycosylated heterodimeric protein that is constitutively secreted and referred to as soluble clusterin (sCLU), when found in association with lipoproteins which by far we already know are shorter forms of the precursor CLU have been detected intracellularly and named cytosolic, truncated or nuclear CLU [33][34][35].The function of intracellular CLU (iCLU) is not completely understood. Of relevance to AD, it has been recently shown that iCLU levels increase quickly in cultured primary neurons exposed to amyloid-b peptides (Ab), and that this iCLU elevation is required for the neurotoxic downstream signaling effects of Ab [36].…”
Section: Clusterin In Neurodegenerative Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Its strongest association was found for the common single nucleotide polymorphism (SNP) rs11136000 located in a non-coding, intronic CLU region [32]. CLU expression is highest in the brain and is markedly up regulated under situations of stress and inflammation .This gives rise to glycosylated heterodimeric protein that is constitutively secreted and referred to as soluble clusterin (sCLU), when found in association with lipoproteins which by far we already know are shorter forms of the precursor CLU have been detected intracellularly and named cytosolic, truncated or nuclear CLU [33][34][35].The function of intracellular CLU (iCLU) is not completely understood. Of relevance to AD, it has been recently shown that iCLU levels increase quickly in cultured primary neurons exposed to amyloid-b peptides (Ab), and that this iCLU elevation is required for the neurotoxic downstream signaling effects of Ab [36].…”
Section: Clusterin In Neurodegenerative Disordersmentioning
confidence: 99%
“…In humans, at least two distinct CLU mRNA isoforms that differ in their unique exon I exist as a result of alternative transcriptional initiation start sites, (Isoform 1, NM_001831.2 and Isoform 2, NM_203339.1).These two transcripts are probably originated from two transcriptional initiation start sites and only produced in humans and chimpanzees. Both isoforms contain 9 exons (and 8 introns) and a terminal 5'-untranslated region [13].The mRNA isoform 1 is a major form of CLU mRNA, whereas other forms comprising mRNA isoform 2 account for <1% of total CLU mRNA [14]. This protein is then directed to the lumen of the endoplasmic reticulum by a leader signaling sequence and further undergoes an extensive N-linked glycosylation process, where it becomes a 75-80kDa mature precursor after transportation from the endoplasmic reticulum (ER) to the Golgi apparatus [15].Six N-linked Glycosylation sites of human CLU were identified by Kapron, three on the alpha chain (α 64N, α 81N, α 123N) and three on the beta chain (β 64N, β 127N, β 147N) [16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, CLU gene can be transcribed into at least three mRNA variants (NCBI Reference No. : NM_001831.3; NR_038335.1; NR_045494.1) or perhaps even more [3]. The mRNA isoform 1 is a major form of CLU mRNA, whereas other forms including mRNA isoform 2 collectively count for less than 1% of total CLU mRNA [3].…”
mentioning
confidence: 99%
“…: NM_001831.3; NR_038335.1; NR_045494.1) or perhaps even more [3]. The mRNA isoform 1 is a major form of CLU mRNA, whereas other forms including mRNA isoform 2 collectively count for less than 1% of total CLU mRNA [3]. Two isoforms of CLU proteins have been well characterized; nuclear isoform of CLU (nCLU, isoform 1) containing the nuclear localization signal that is translated due to the splicing at exon 1 and 3 together placing a downstream AUG at exon 3 as the first available translation and lacking of exon 2 [3,4], while pre-secreted isoform of CLU (sCLU) containing the endoplasmic reticulum (ER)-targeting signalencoding in exon 2 [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation